Faktor yang Berhubungan dengan Kebiasaan Merokok pada Santri Panti Asuhan - Kassaming Kassaming; Ibrahim Ibrahim (Universitas 'Aisyiyah Yogyakarta, 2018)
Indonesian smokers spend 225 billion cigarettes every year. This research used the cross sectional study that aim to know the factors influenced the smoking habits of Islamic Orphanage's students in Sidenreng Rappang Regency at 2017. Sample of this research was 50 students. Sampling technique using stratified proporsional sampling from all Islamic Orphanages in Sidenreng Rappang Regency. The result of this research from four research variables showed that the students smoke not influenced by the variables. So, the researchers conclude to do research with differents variables. There is possibility that the students smoke because other variables.